PENGUATAN DAYA SAING UMKM MELALUI DIGITALISASI DAN INOVASI PRODUK DALAM MENINGKATKAN PEREKONOMIAN LOKAL - A. Taufiq Hidayat; Khalilah Daud Isaac Makhmut; Laila Nur Azizah (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyse the strategy of digitalisation and product innovation in improving the sustainability and competitiveness of MSMEs in Indonesia. This research uses mixed methods (qualitative and quantitative) to obtain comprehensive data. The research involved 10 MSME players representing various sectors, such as culinary, fashion, computer, and services. The research was conducted on MSMEs in the Bojonegoro area. Data Collection Techniques 1) Questionnaires, 2) In-depth Interview, 3) Field Observation. Data Analysis Technique using SWOT analysis to evaluate the strengths, weaknesses, opportunities, and threats faced by MSMEs. A total of 8 out of 10 MSMEs claimed to have made product innovations, both in the form of packaging, variations in taste/colour, and development of services based on customer needs.Innovations are based on direct customer feedback or through social media. However, only 4 MSMEs conducted regular and structured innovations. Most MSMEs reported an increase in turnover and market reach after implementing digitalisation and product innovation. For example, three culinary MSMEs managed to increase their daily transactions by 40 per cent through QRIS. Another fashion MSME managed to reach buyers from outside the region after uploading a product catalogue on a marketplace. The results of the SWOT analysis indicate that :1. Strengths Unique and locally-based products, proximity to local markets: Emotional and social relationships with local consumers create customer loyalty, High spirit of innovation. 2. Weaknesses: Limited digital literacy: Most MSME players do not understand digital platforms such as e-commerce and digital payments. 3. Opportunities Growth of internet users and e-commerce: Increased online shopping behaviour opens up new markets for local products. 4. Threats: Competition from products outside the region or abroad: Cheaper mass products from outside can threaten the local market. Conclusion: Digitalisation and product innovation are proven to improve the competitiveness of MSMEs in Bendo, Bojonegoro Regency. Despite uneven implementation, preliminary results show an increase in turnover, market expansion, and positive contribution to the local economy.